Biodegradation of Phenanthrene and Heavy Metal Removal by Acid-Tolerant Burkholderia fungorum FM-2 - Liu, Xin-xin; Hu, Xin; Cao, Yue; Pang, Wen-jing; Huang, Jin-yu; Guo, Peng; Huang, Lei (Frontiers in Microbiology, 2019)
Phenanthrene (PHE) is a common pollutant of acidic and non-acidic environments that is recalcitrant to biodegradation. Herein, Burkholderia fungorum FM-2 was isolated from oil-contaminated soil in Xinjiang and characterised morphologically, physiologically and phylogenetically. Environmental parameters including PHE concentration, pH, temperature and salinity were optimised, and heavy metal tolerance was investigated. Atypically for a B. fungorum strain, FM-2 utilised PHE (300 mg L-1) as a sole carbon source over a wide pH range (between pH 3 and 9). PHE and heavy metal metabolism were assessed using gas chromatography (GC), inductively coupled plasma optical emission spectroscopy (ICP-OES), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS), Fourier-transform infrared (FTIR) spectroscopy and ultraviolet (UV) absorption spectrometry. The effects of heavy metals on the bioremediation of PHE in soil were investigated, and the findings suggest that FM-2 has potential for combined bioremediation of soils co-contaminated with PHE and heavy metals.